Constant DC output boost converter for solar system sourace model - Eldagdag, Nabil Musbah (2013)
A Neural network controller of DC-DC boost converter is designed and presented in this project. In order to control the output voltage of the boost converter, the controller is designed to change the duty cycle of the converter. The mathematical model of boost converter and neural network controller are derived to design simulation model. The simulation is developed on Matlab simulation program. To verity the effectiveness of the simulation model, an experimental set up is developed. The boost circuit with mosfet as a switching component is developed. The neural network controller to generate duty cycle of PWM signal is programmed. The simulation and experimental results show that the output voltage of the boost converter can be controlled according to the value of duty cycle.